About the transition to an eco-compatible society: the example of urban spread. - Lefebvre, Olivier (My University, 2018)
The transition to an eco-compatible society will depend on the conclusions of many "logical duels", to use the words of the French sociologist Tarde. Therefore, to make prospective is uneasy: the logical duels of the day after tomorrow will depend on the conclusions of the logical duels of tomorrow, which are unknown. However, in this framework one can state what this transition will not be: (1) BAU (Business As Usual) is impossible (2) to take into account the stake of the metabolism of cities, only, is not enough (3) an Ecological Cultural Revolution is improbable. It seems that two logical duels matter very much: demography (the answer to the question: "how many do we want to be?") and quality of life (the answer to the question: "do we want, or not, quality of life?"). Therefore one can build two scenarios, ecological emergency (in case of high population growth) and quality of life. Concerning several stakes (energy, water, agriculture...) the choices which are made in each scenario are different. In each scenario there is struggle against urban spread but for different reasons: in the scenario "ecological emergency" countryside is a reservoir of indispensable resources, in the scenario "quality of life" countryside is a place to preserve (use for leisure, quality of landscapes..).
Keywords: Verstädterung; Stadtentwicklung; Strukturwandel; Sozialwandel; Demographischer Wandel; Transformation; Nachhaltige Entwicklung; Umweltverträglichkeit; Planungsphilosophie; Prognose; Szenario